1997
DOI: 10.1083/jcb.138.6.1355
|View full text |Cite
|
Sign up to set email alerts
|

Myelin-associated Glycoprotein Interacts with Neurons via a Sialic Acid Binding Site at ARG118 and a Distinct Neurite Inhibition Site

Abstract: Inhibitory components in myelin are largely responsible for the lack of regeneration in the mammalian CNS. Myelin-associated glycoprotein (MAG), a sialic acid binding protein and a component of myelin, is a potent inhibitor of neurite outgrowth from a variety of neurons both in vitro and in vivo. Here, we show that MAG's sialic acid binding site is distinct from its neurite inhibitory activity. Alone, sialic acid–dependent binding of MAG to neurons is insufficient to effect inhibition of axonal growth. Thus, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
123
0
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 137 publications
(131 citation statements)
references
References 42 publications
6
123
0
2
Order By: Relevance
“…It is also a sialic acid-binding protein, and its first four Ig-like domains are homologous to those of other sialic acid binding, Ig-like LECTINS (Siglecs), so it is also a member of the Siglec family (Siglec4a) 24 . The sialic acid binding capabilities of Mag are not essential for it to exert inhibition 25 , but they are likely to potentiate the effect (see later in text and BOX 2). Mag is found in both the CNS and the PNS, where it is located in the periaxonal membrane, and is therefore ideally placed to interact with an axonal receptor.…”
Section: Receptors For Inhibitors Of Axonal Growthmentioning
confidence: 99%
“…It is also a sialic acid-binding protein, and its first four Ig-like domains are homologous to those of other sialic acid binding, Ig-like LECTINS (Siglecs), so it is also a member of the Siglec family (Siglec4a) 24 . The sialic acid binding capabilities of Mag are not essential for it to exert inhibition 25 , but they are likely to potentiate the effect (see later in text and BOX 2). Mag is found in both the CNS and the PNS, where it is located in the periaxonal membrane, and is therefore ideally placed to interact with an axonal receptor.…”
Section: Receptors For Inhibitors Of Axonal Growthmentioning
confidence: 99%
“…It has also been reported that soluble dMAG species secreted from damaged white matter are able to inhibit axonal regeneration (Tang et al, 2001;Tang et al, 1997b). This inhibition appears to require both the presence of a sialic acid binding site at R118 within the first Ig domain as well as a second, unknown site (Tang et al, 1997a). The R118 site is present within an RGD sequence (Fig.…”
Section: Mmp-7 Generated Mag Fragments Inhibit Neuronal Process Outgrmentioning
confidence: 80%
“…Cleavage at either Leu 509 or Met 234 would potentially release an N terminal fragment that includes the sialic-acid binding domain which is critical to the neurite outgrowth inhibitory effect of dMAG (Tang et al, 1997a). To assess the bioactivity of soluble MMP-generated MAG fragments, specifically the effects on neuronal process growth, we used Campenot chambers (Campenot, 1977).…”
Section: Mmp-7 Generated Mag Fragments Inhibit Neuronal Process Outgrmentioning
confidence: 99%
“…It was previously shown that soluble MAG, released in abundance from myelin and found in vivo, and MAG-Fc could potently inhibit axonal growth. 12,13 Our results revealed that soluble MAG-Fc (25 mg/ml) triggered Rap1 activation from 10 min to 4 h after its addition into the medium (Figure 1a). In contrast, the activity of Ras, another member of the Ras family of small G proteins, was suppressed transiently and returned to the control level at 4 h ( Figure 1a).…”
Section: Resultsmentioning
confidence: 84%
“…12,13 It is also possible that the transport of p75 in complex with Rap1 does not require the internalization of MAG.…”
Section: Discussionmentioning
confidence: 99%